Composite materials for microwave devices using additive manufacturing. Issue 10 (1st May 2016) - Bukhari, S.S.; Whittow, W.G.; Zhang, S.; Vardaxoglou, J.C.
Abstract : Additive manufacturing has been combined with commercially available RF materials to synthesise composite materials whose relative permittivity can be controlled. A design equation for predicting the effective permittivity of these composite materials has also been presented. The relative permittivity of the composite materials was measured by fabricating patch antennas using these materials as the substrate. It has been demonstrated that by using Taconic, polyactic acid (PLA) and air, three materials with different dielectric constants, a large and nearly continuous range of relative permittivity values, from 1.47 to 6.00, can be realised.